Silver-substituted (Ag1-xCux)2ZnSnS4 solar cells from aprotic molecular inks. Issue 15 (1st August 2022) - Engberg, Sara; Gansukh, Mungunshagai; Martinho, Filipe; Stamate, Eugen; Hansen, Ole; Schou, Jørgen; Canulescu, Stela
Abstract: To battle the high open-circuit voltage deficit (VOC, def ) in kesterite (Cu2 ZnSnS4 or CZTS) solar cells, a current field of research relates to point defect engineering by cation substitution. For example, by partly replacing Cu with an element of a larger ionic radius, such as Ag, the degree of Cu/Zn disorder decreases, and likewise does the associated band tailing. In this paper, solution-processed (Ag1-x Cux )2 ZnSnS4 (ACZTS) samples are prepared through the aprotic molecular ink approach using DMSO as the solvent. The successful incorporation of silver into the CZTS lattice is demonstrated with relatively high silver concentrations, namely Ag/(Ag+Cu) ratios of 13% and 26%. The best device was made with 13% Ag/(Ag+Cu) and had an efficiency of 4.9%. The samples are compared to the pure CZTS sample in terms of microstructure, phase distribution, photoluminescence, and device performance. In the XRD patterns, a decrease in the lattice parameter c/a ratio is observed for ACZTS, as well as significant peak splitting with Ag addition for several of the characteristic kesterite XRD reflections. In addition to the improvement in efficiency, other advantageous effects of Ag-incorporation include enhanced grain growth and an increased band gap. A too high concentration of Ag leads to the formation of secondary phases such as SnS and Ag2 S as detected by XRD.